socio-economic effects of climate change in Peru (2006-2011) - Ramírez Bautista, Durga Edelmira (2012)
The main objective of the study is to determine the socio-economic impact of Climate Change in Peru between the years 2006 to 2011. To achieve the objective methods were used for analysis, synthesis and Delphi technique was applied to experts. We describe the most important economic and social consequences of climate change as a result of vulnerability presented by Peru and the climatic and environmental changes that suffer. In relation to current public policy, it is observed that while progress has been made to address climate change, it would put too much emphasis on mitigation, at the expense of adaptation to climate change, which does not adequately reflect the country’s vulnerability to the same. We propose a proactive policy with emphasis on adaptation measures aimed at adjusting the natural and human systems in response to perturbations generated by climate change, allowing moderate its ill effects or even take advantage of profit opportunities they create.